Patch Testing to Identify Allergens Causing Pigmented Contact Dermatitis: A Retrospective Study - Shini Choubey; Nithya Satish; Chakravarthi R. Srinivas; Farheen Begum (Indian Dermatology Online Journal)
Background: One of the prevalent dermatological conditions identified among Indian patients visiting dermatology clinics is pigmented contact dermatitis (PCD). The gold standard for diagnosing PCD is patch testing. The allergen that results in PCD and its clinico-demographic pattern could differ. Identifying the common allergens will help the clinician while treating cases with PCD. Aim and Objective: To determine the clinico-demographic distribution of PCD and to establish the common allergens that are responsible by patch testing. Patients and Methods: The study included 30 patients with PCD. All patient’s clinico-demographic profiles were recorded. The extended Indian Standard Series kit comprising of 56 antigens was used for patch testing in the outpatient department. In addition, patch testing was done with a few brands of kumkum, sacred ash, sandalwood paste, and patients own material where it was indicated. The patch test was performed and interpreted as recommended by the International Contact Dermatitis Research Group. Results: The male: female ratio was 1:1.7. In 21 patients (70%), face was the most common site of pigmentation. The most frequently related symptom was pruritus. Out of the 30 patients, the patch test was positive in 25 (83.3%) of the cases. Paraphenylenediamine (PPD) and fragrance mix were found to be the most common allergens in 7 (28%) and 6 (24%) patients, respectively. In 13 patients (52.2%), reaction was observed with two or more allergens. Limitation: The above study, followed by photo-patch testing, may have detected more allergens inducing PCD. The photo-patch test was not performed due to non-availability of allergens. Conclusion: PPD is the most common allergen implicated, followed by fragrances.